Preparation method of high-compaction high-quality energy density lithium iron phosphate
Patent Information
- Application Number
- CN202210724854.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-23
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2042-06-23
AI Technical Summary
该方案对于磷酸铁铁磷比的选择具有极高的要求,商业化实现难度大
[0031]本发明在磷酸铁锂制备过程的中间体阶段,采用六甲基磷酰三胺作为包覆剂,有助于诱导磷酸铁锂的晶体长大,实现磷酸铁锂颗粒的大小掺混,形成具有多级粒度级配的磷酸铁锂,提高磷酸铁锂的压实密度。六甲基磷酰三胺在氮气氛围烧结的过程中,还能够提高磷酸铁锂表面碳层与磷酸铁锂材料结合的致密性,使碳层在磷酸铁锂粉碎过程中不易被破坏,进一步提高磷酸铁锂材料的能量密度,降低粉体电阻率。本发明方法,具有制备工艺操作简单,制造成本低的特点。
Smart Images

Figure CN117317154B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing high-pressure, high-energy-density lithium iron phosphate with optimized particle size distribution, belonging to the field of lithium battery cathode material preparation. Background Technology
[0002] Lithium-ion batteries, with their advantages of high energy density, long lifespan, no memory effect, and high operating voltage, have become the main development direction for portable energy storage and power batteries. The cathode material is a key factor determining the cost, safety, and electrochemical performance of lithium-ion batteries. Lithium iron phosphate, belonging to the olivine-type lithium transition metal phosphate family, has become one of the mainstream cathode materials for lithium batteries due to its outstanding advantages such as low cost, environmental friendliness, abundant raw material reserves, high safety, and stable operating voltage.
[0003] While the stable crystal structure of lithium iron phosphate (LFP) materials improves safety, it also suffers from low electronic conductivity and lithium-ion mobility, severely impacting its electrochemical performance, specifically its mass energy density. Through extensive research, researchers have employed techniques such as nanostructuring, carbon coating, and elemental doping to significantly improve the mass energy density of LFP materials. The theoretical specific capacity of LFP is 170 mAh / g, while currently commercially available products achieve a specific capacity of 160 mAh / g (0.1C, 25℃), very close to the theoretical energy density.
[0004] With the increasing demands for driving range in electric vehicles, the energy density of lithium iron phosphate (LFP) batteries is once again facing challenges. With the mass energy density approaching the theoretical value, further improving the volumetric energy density has become a key research focus. An important indicator for measuring volumetric energy density is powder compaction density; currently, the compaction density of commercially available products is mostly between 2.35-2.6 g / cm³. 3 The theoretical density of lithium iron phosphate is 3.6 g / cm³. 3 There is huge potential for increasing compaction density.
[0005] Existing technologies mainly achieve high-compaction lithium iron phosphate products through the following methods: First, by controlling the particle size during milling, differences in the size of the lithium iron phosphate product are created, thereby achieving high compaction. This method is cumbersome, and the compaction of the two particle sizes is relatively low, often less than 2.6 g / cm³, as seen in patents CN202111046942.X and CN202010117579.5. Second, by selecting iron phosphate raw materials with high and low iron-to-phosphorus ratios, the product's particle size can be mixed and high-compacted, as seen in patent CN201811397958.3. This method has extremely high requirements for the selection of the iron-to-phosphorus ratio, making commercial implementation difficult. Summary of the Invention
[0006] To address the aforementioned problems in the existing technology, this invention provides a high-compact, high-energy-density lithium iron phosphate (LFP) preparation method. This method introduces hexamethylphosphoric triamine as a coating agent during the intermediate stage of LFP preparation. This assists in inducing LFP crystal growth and improves the density of the bond between the carbon layer on the LFP surface and the LFP material. This achieves particle size mixing after pulverization, optimizes particle size distribution, thereby increasing the compaction density of LFP and ultimately enhancing its volumetric energy density.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0008] This invention provides a method for preparing high-pressure, high-energy-density lithium iron phosphate, comprising the following steps:
[0009] 1) Iron phosphate, lithium source, carbon source, titanium dopant and solvent are mixed to form a slurry, which is then milled into nano-sized particles and spray-dried to obtain lithium iron phosphate precursor;
[0010] 2) Spray hexamethylphosphoric triamine onto the surface of the lithium iron phosphate precursor and mix evenly to obtain hexamethylphosphoric triamine-coated lithium iron phosphate precursor;
[0011] 3) The lithium iron phosphate precursor coated with hexamethylphosphoric triamine was calcined in a nitrogen atmosphere and then pulverized to obtain high-pressure, high-energy-density lithium iron phosphate.
[0012] In step 1) of the present invention, the iron phosphate has an iron-to-phosphorus ratio of 0.955-1:1, preferably 0.965-0.975;
[0013] The lithium source is selected from lithium carbonate and / or lithium hydroxide;
[0014] The carbon source is selected from any one or a combination of at least two of glucose, sucrose, starch, polyethylene glycol, polyvinyl alcohol, and polyacrylic acid, preferably any one or a combination of at least two of glucose, sucrose, and polyethylene glycol;
[0015] The titanium dopant is selected from any one or a combination of at least two of titanium oxide, titanium tetrachloride, titanium sulfate, isopropyl titanate, and isobutyl titanate, preferably any one or a combination of at least two of titanium oxide, isopropyl titanate, and isobutyl titanate.
[0016] The solvent is selected from water, ethanol or methanol.
[0017] In step 1) of this invention, the mass ratio of iron phosphate to lithium source, carbon source, and titanium dopant is 100:24-26:10-15:0.13-0.53;
[0018] The amount of solvent used, based on the solid content of the prepared slurry, is 30-50 wt%, preferably 35-45 wt%.
[0019] In step 1) of the present invention, the particle size of the slurry after sand milling is controlled at D50 = 200-700nm, preferably 300-500nm.
[0020] In step 1) of this invention, the particle size of the lithium iron phosphate precursor is controlled at D50 = 15-80 μm, preferably 30-60 μm. After sand milling, the nano-sized particle slurry can be agglomerated by spray drying to form micron-sized secondary particles, which are spherical, i.e., lithium iron phosphate precursor.
[0021] In step 2) of the present invention, the amount of hexamethylphosphoric triamine is 0.5-5 wt% of the precursor mass, preferably 1-4 wt%.
[0022] Preferably, when spraying the hexamethylphosphoric triamine, the spray pressure is 1-3 MPaG, the droplet diameter is controlled to be ≤0.5 mm, and the spraying time is ≥30 min, preferably 30-60 min, to ensure the uniformity of spraying.
[0023] In step 2) of this invention, the equipment used for mixing is selected from a double cone mixer, a three-dimensional mixer, a planetary mixer, a ribbon mixer, or a super mixer.
[0024] In step 3) of this invention, the nitrogen atmosphere has a nitrogen purity of ≥99.9995% and a pressure of 20-50 PaG.
[0025] In step 3) of this invention, the roasting temperature is 750-800℃ and the holding time is 8-12h.
[0026] The high-pressure, high-energy-density lithium iron phosphate prepared by the method of this invention has a particle size range of D10 = 0.3-0.5 μm, D50 = 1-5 μm, and D90 ≤ 5 μm.
[0027] The high-density lithium iron phosphate powder prepared by the method of this invention has a compaction density ≥2.60 g / cm³. 3 The specific capacity (i.e., gravimetric energy density) of the button cell is ≥156mAh / g (0.1C, 25℃), and the powder resistivity is ≤20Ω·mm.
[0028] The method of this invention, in the intermediate stage of lithium iron phosphate preparation, employs a spray-mixing method to coat the surface of the precursor (secondary spherical particles) formed by spray drying with hexamethylphosphoric triamine (e.g., ... Figure 1(As shown). During the calcination process, the lithium iron phosphate precursor coated with hexamethylphosphoric acid triamine reacts with lithium carbonate to form lithium iron phosphate. At this time, the iron phosphate on the surface of the precursor comes into contact with hexamethylphosphoric acid triamine, and the phosphorus-oxygen bonds in hexamethylphosphoric acid triamine and the phosphorus-oxygen bonds in iron phosphate form strong chemical bonds, inducing the accelerated growth of lithium iron phosphate grains located on the outer surface of the spherical particles. Moreover, the closer to the surface of the spherical particles, the larger the lithium iron phosphate particles are. Finally, under the action of air jet milling, the secondary spherical particles of this structure are broken down, which can form lithium iron phosphate powder with the multi-level particle size distribution of the present invention, thereby obtaining a high-compacted lithium iron phosphate product.
[0029] Furthermore, during the calcination process in a nitrogen atmosphere, hexamethylphosphoric triamine can form a carbon layer structure that is densely bonded to lithium iron phosphate crystals due to the strong chemical bond between the phosphorus and oxygen in the coating agent. This structure works synergistically with the main carbon source to increase the density of the carbon layer on the lithium iron phosphate surface and the lithium iron phosphate material, making the carbon layer less susceptible to damage during the lithium iron phosphate pulverization process. At the same time, it further improves the energy density of the lithium iron phosphate material and reduces the resistivity of the powder.
[0030] Compared with existing technologies, the advantages of the technical solution of this invention are as follows:
[0031] In the intermediate stage of lithium iron phosphate (LFP) preparation, this invention uses hexamethylphosphoric triamine as a coating agent, which helps induce LFP crystal growth, achieves particle size mixing, and forms LFP with multi-level particle size distribution, thereby increasing the compaction density of LFP. During nitrogen atmosphere sintering, hexamethylphosphoric triamine also improves the density of the bond between the carbon layer on the LFP surface and the LFP material, making the carbon layer less susceptible to damage during LFP pulverization, further increasing the energy density of the LFP material and reducing the powder resistivity. This invention's method features simple preparation process and low manufacturing cost. Attached Figure Description
[0032] Figure 1 This is a schematic diagram illustrating the growth of lithium iron phosphate crystals induced by hexamethylphosphoric acid triamine.
[0033] Figure 2 The particle size distribution diagram is shown for the lithium iron phosphate product prepared in Example 1.
[0034] Figure 3 SEM image of the lithium iron phosphate product prepared in Example 1;
[0035] Figure 4 The particle size distribution diagram of the lithium iron phosphate product prepared in Comparative Example 1;
[0036] Figure 5 SEM image of the lithium iron phosphate product prepared for Comparative Example 1. Detailed Implementation
[0037] The present invention will now be described in conjunction with specific embodiments. It should be noted that the embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-substantial improvements and adjustments made to the present invention based on its content are within the scope of protection of the present invention.
[0038] The sources of the reagents and raw materials used in the embodiments and comparative examples of this invention are shown in the table below. Unless otherwise specified, all other reagents and raw materials are commercially available products.
[0039] 1 Ferric phosphate Iron-to-phosphorus ratio = 0.955-1 Aladdin 2 lithium carbonate Industrial grade and above Aladdin 3 Hexamethylphosphoric acid triamide Purity > 98% Aladdin 4 Titanium dioxide Purity > 99% Aladdin 5 Glucose (monohydrate) 98% purity Aladdin
[0040] The test methods used in the embodiments and comparative examples of this invention are as follows:
[0041] Particle size distribution: tested using Malvern MS3000.
[0042] Compacted density: Tested using the Sansi Test UTM7305.
[0043] Specific capacity (mass energy density) of button cells: The button cells were prepared and tested using a Newway tester, with a voltage range of 2.0V to 3.75V.
[0044] Powder resistivity: Tested using a Derek FT-7200A.
[0045] Example 1
[0046] Preparation of high-pressure, high-energy-density lithium iron phosphate:
[0047] 1) Iron phosphate (iron-to-phosphorus ratio 0.965), lithium carbonate, glucose, and titanium dioxide were prepared in a mass ratio of 100:25:12.5:0.4, and then mixed with water to form a slurry with a solid content of 40wt%. The slurry was then milled to a particle size of D50 = 500 nm. The milled slurry was then dried using a spray dryer to obtain the lithium iron phosphate precursor with a particle size of D50 = 30 μm.
[0048] 2) Hexamethylphosphoric acid triamine (2.5 wt% by weight) was sprayed onto the surface of the lithium iron phosphate precursor at a spray pressure of 2 MPaG. The droplet diameter was controlled to be ≤0.5 mm, and the spraying time was controlled to be 45 min to ensure uniformity. The mixture was then thoroughly mixed using a ribbon mixer to obtain a hexamethylphosphoric acid triamine-coated lithium iron phosphate precursor.
[0049] 3) The hexamethylphosphoric triamine-coated lithium iron phosphate precursor was transferred to a kiln under a nitrogen atmosphere (≥99.995%) for calcination at a furnace pressure of 30 PaG, a calcination temperature of 790℃, and a calcination time of 12h. After solid-state reaction, lithium iron phosphate material was formed, and then it was pulverized to obtain high-pressure, high-energy-density lithium iron phosphate.
[0050] The particle size of lithium iron phosphate products is D10 = 0.36 μm, D50 = 1.58 μm, and D90 = 3.02 μm.
[0051] The compacted density of lithium iron phosphate powder is 2.74 g / cm³. 3 The coin cell has a specific capacity (mass energy density) of 160 mAh / g (0.1C, 25℃) and a powder resistivity of 12 Ω·mm.
[0052] Example 2
[0053] Preparation of high-pressure, high-energy-density lithium iron phosphate:
[0054] 1) Iron phosphate (iron-to-phosphorus ratio 0.955), lithium carbonate, glucose, and titanium dioxide were prepared in a mass ratio of 100:24:15:0.2, and then mixed with water to form a slurry with a solid content of 30wt%. The slurry was then milled to a particle size D50 of 200 nm. The milled slurry was then dried using a spray dryer to obtain the lithium iron phosphate precursor with a particle size D50 of 60 μm.
[0055] 2) Hexamethylphosphoric acid triamine (4.5 wt% by weight) was sprayed onto the surface of the lithium iron phosphate precursor at a spray pressure of 3 MPaG. The droplet diameter was controlled to be ≤0.5 mm, and the spraying time was controlled to be 45 min to ensure uniformity. The mixture was then thoroughly mixed using a ribbon mixer to obtain a hexamethylphosphoric acid triamine-coated lithium iron phosphate precursor.
[0056] 3) The hexamethylphosphoric triamine-coated lithium iron phosphate precursor was transferred to a kiln under a nitrogen atmosphere (≥99.995%) for calcination at a furnace pressure of 25 PaG, a calcination temperature of 770℃, and a calcination time of 10 h. After solid-phase reaction, lithium iron phosphate material was formed, and then it was pulverized to obtain high-pressure, high-energy-density lithium iron phosphate.
[0057] The particle size of lithium iron phosphate products is D10 = 0.41 μm, D50 = 1.60 μm, and D90 = 3.46 μm.
[0058] The compacted density of lithium iron phosphate powder is 2.68 g / cm³. 3 The coin cell has a specific capacity (mass energy density) of 159 mAh / g (0.1C, 25℃) and a powder resistivity of 19 Ω·mm.
[0059] Example 3
[0060] Preparation of high-pressure, high-energy-density lithium iron phosphate:
[0061] 1) Iron phosphate (iron-to-phosphorus ratio 0.989), lithium carbonate, glucose, and titanium dioxide were prepared in a mass ratio of 100:26:10:0.53, and then mixed with water to form a slurry with a solid content of 45 wt%. The slurry was then milled to a particle size D50 of 600 nm. The milled slurry was then dried using a spray dryer to obtain the lithium iron phosphate precursor with a particle size D50 of 25 μm.
[0062] 2) Spray 0.5 wt% hexamethylphosphoric triamine onto the surface of the lithium iron phosphate precursor using a spray method. The spray pressure is 1 MPaG, the droplet diameter is controlled to be ≤0.5 mm, and the spraying time is controlled to be 45 min to ensure uniformity. The mixture is then thoroughly mixed using a ribbon mixer to obtain a hexamethylphosphoric triamine-coated lithium iron phosphate precursor.
[0063] 3) The hexamethylphosphoric acid triamine-coated lithium iron phosphate precursor was transferred to a kiln under a nitrogen atmosphere (≥99.995%) for calcination at a furnace pressure of 35 PaG, a calcination temperature of 760℃, and a calcination time of 8h. After solid-phase reaction, lithium iron phosphate material was formed, and then it was pulverized to obtain high-pressure, high-energy-density lithium iron phosphate with excellent particle size distribution.
[0064] The particle size of lithium iron phosphate products is D10 = 0.45 μm, D50 = 1.71 μm, and D90 = 3.86 μm.
[0065] The compacted density of lithium iron phosphate powder is 2.65 g / cm³. 3 The coin cell has a specific capacity (mass energy density) of 161 mAh / g (0.1C, 25℃) and a powder resistivity of 11 Ω·mm.
[0066] Comparative Example 1
[0067] The method is the same as in Example 1, except that step 2) is omitted. That is, the lithium iron phosphate precursor prepared in step 1) is not coated with hexamethylphosphoric triamine, and the lithium iron phosphate product is obtained directly by step 3).
[0068] The particle size of lithium iron phosphate products is D10 = 0.26 μm, D50 = 1.33 μm, and D90 = 5.09 μm.
[0069] The compacted density of lithium iron phosphate powder is 2.45 g / cm³. 3 The coin cell has a specific capacity (mass energy density) of 158 mAh / g (0.1C, 25℃) and a powder resistivity of 54 Ω·mm.
[0070] Comparative Example 2
[0071] Referring to the method of Example 1, the difference is that step 2) is omitted, and hexamethylphosphoric acid triamine is added to the slurry of step 1, and the lithium iron phosphate product is obtained directly by step 3).
[0072] The particle size of lithium iron phosphate products is D10 = 0.51 μm, D50 = 1.73 μm, and D90 = 6.1 μm.
[0073] The compacted density of lithium iron phosphate powder is 2.67 g / cm³. 3 The coin cell has a specific capacity (mass energy density) of 155.8 mAh / g (0.1C, 25℃) and a powder resistivity of 21 Ω·mm.
[0074] Comparative Example 3
[0075] The method is the same as in Example 1, except that hexamethylphosphoric triamine is replaced with hexaethylphosphoric triamine.
[0076] The particle size of lithium iron phosphate products is D10 = 0.22 μm, D50 = 1.23 μm, and D90 = 3.89 μm.
[0077] The compacted density of lithium iron phosphate powder is 2.54 g / cm³. 3 The coin cell has a specific capacity (mass energy density) of 158 mAh / g (0.1C, 25℃) and a powder resistivity of 28 Ω·mm.
Claims
1. A method for preparing high-pressure, high-energy-density lithium iron phosphate, characterized in that the steps include... include: 1) Iron phosphate, lithium source, carbon source, titanium dopant and solvent are mixed to form a slurry, which is then milled into nano-sized particles and spray-dried to obtain lithium iron phosphate precursor; 2) Spray hexamethylphosphoric triamine onto the surface of the lithium iron phosphate precursor and mix evenly to obtain hexamethylphosphoric triamine-coated lithium iron phosphate precursor; 3) The lithium iron phosphate precursor coated with hexamethylphosphoric triamine was calcined in a nitrogen atmosphere and then pulverized to obtain high-pressure, high-energy-density lithium iron phosphate. In step 1), the particle size of the lithium iron phosphate precursor is controlled at D50 = 15-80 μm; in step 2), the amount of hexamethylphosphoric acid triamine is 0.5-5 wt% of the precursor mass.
2. The preparation method according to claim 1, characterized in that, In step 1), the iron phosphate has an iron-to-phosphorus ratio of 0.955-1:1; The lithium source is selected from lithium carbonate and / or lithium hydroxide; The carbon source is selected from any one or a combination of at least two of glucose, sucrose, starch, polyethylene glycol, polyvinyl alcohol, and polyacrylic acid; The titanium dopant is selected from any one or a combination of at least two of titanium oxide, titanium tetrachloride, titanium sulfate, isopropyl titanate, and isobutyl titanate.
3. The preparation method according to claim 2, characterized in that, The iron phosphate has an iron-to-phosphorus ratio of 0.965-0.
975.
4. The preparation method according to claim 1, characterized in that, In step 1), the mass ratio of iron phosphate to lithium source, carbon source and titanium dopant is 100:24-26:10-15:0.13-0.
53.
5. The preparation method according to claim 1, characterized in that, In step 1), the solvent is selected from water, ethanol, or methanol; The amount of solvent used, based on the solid content of the prepared slurry, is 30-50 wt%.
6. The preparation method according to claim 5, characterized in that, The amount of solvent used, based on the solid content of the prepared slurry, is 35-45 wt%.
7. The preparation method according to claim 1, characterized in that, In step 1), the particle size of the slurry after sand milling is controlled at D50=200-700nm.
8. The preparation method according to claim 7, characterized in that, The particle size of the slurry after sand milling is controlled at D50=300-500nm.
9. The preparation method according to claim 7, characterized in that, The particle size of the lithium iron phosphate precursor is controlled at D50 = 30-60 μm.
10. The preparation method according to claim 1, characterized in that, The amount of hexamethylphosphoric triamine used is 1-4 wt% of the precursor mass.
11. The preparation method according to claim 1, characterized in that, In step 2), when spraying the hexamethylphosphoric triamine, the spray pressure is 1-3 MPaG, the droplet diameter is controlled to be ≤0.5 mm, and the spraying time is ≥30 min.
12. The preparation method according to claim 11, characterized in that, Spraying time is 30-60 minutes.
13. The preparation method according to claim 1, characterized in that, In step 2), the equipment used for mixing is selected from a double cone mixer, a three-dimensional mixer, a planetary mixer, a ribbon mixer, or a super mixer.
14. The preparation method according to claim 1, characterized in that, In step 3), the nitrogen atmosphere has a nitrogen purity of ≥99.9995% and a pressure of 20-50 PaG.
15. The preparation method according to claim 1, characterized in that, In step 3), the roasting temperature is 750-800℃ and the holding time is 8-12h.
16. A high-pressure, high-energy-density lithium iron phosphate prepared by the method according to any one of claims 1-15, characterized in that, The particle size range is D10=0.3-0.5μm, D50=1-5μm, and D90≤5μm; The high-density, high-energy-density lithium iron phosphate powder has a compaction density ≥ 2.60 g / cm³. 3 At 0.1C and 25℃, the coin cell has a specific capacity of ≥156mAh / g and a powder resistivity of ≤20Ω·mm.
Citation Information
Patent Citations
Lithium iron phosphate and preparation method thereof
CN109650366A
Preparation method of high-compaction lithium iron phosphate
CN111392705A
Nanometer lithium iron phosphate with high capacity, high compaction density and high iron-phosphorus ratio, and preparation method of nanometer lithium iron phosphate
CN113716542A
Negative electrode material for lithium battery and lithium battery
CN101373827A
Method for preparing high-density lithium ferric phosphate
CN102009970A